1983
DOI: 10.1111/j.1365-2125.1983.tb01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein binding of non‐steroidal anti‐inflammatory drugs in plasma and synovial fluid of arthritic patients.

Abstract: 1 The protein binding of seven non‐steroidal anti‐inflammatory drugs (indomethacin, tolmetin, salicylic acid, ibuprofen, flurbiprofen, naproxen and GP53,633) and warfarin was investigated by equilibrium dialysis in simultaneous samples of synovial fluid and plasma from 12 arthritic patients. 2 The protein binding of all drugs studied except warfarin and flurbiprofen was significantly lower in synovial fluid than in plasma. 3 The decreased protein binding of these drugs is likely to explain the lower total drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Moreover, it has often been shown that the protein concentration greatly affects the free fraction of drugs, since protein binding is reduced in diseases associated with hyp~albuminemia,~~,~'.~~ and is less in synovial fluid than in plasma, corresponding to the difference in protein concentrations between these media. 21, 32 In the case of our study, none of these explanations can be valid, since the number of molecule.of ligand bound per molecule of albumin increases with increasing albumin concentration except at 20 and 40 gfiter HSA, where the ketoprofen binding was proportional to the protein concentration. The results obtained at 20 and 40 ghter confirmed those obtained in a protein binding study of salicylate.…”
Section: Plasma Protein Binding Of Ketoprofenmentioning
confidence: 66%
“…Moreover, it has often been shown that the protein concentration greatly affects the free fraction of drugs, since protein binding is reduced in diseases associated with hyp~albuminemia,~~,~'.~~ and is less in synovial fluid than in plasma, corresponding to the difference in protein concentrations between these media. 21, 32 In the case of our study, none of these explanations can be valid, since the number of molecule.of ligand bound per molecule of albumin increases with increasing albumin concentration except at 20 and 40 gfiter HSA, where the ketoprofen binding was proportional to the protein concentration. The results obtained at 20 and 40 ghter confirmed those obtained in a protein binding study of salicylate.…”
Section: Plasma Protein Binding Of Ketoprofenmentioning
confidence: 66%
“…Thus, the protein binding is less in diseases associated with hypoalbuminaemia, such as rheumatoid arthritis (Netter et al 1984). In the same manner, the lower binding in synovial fluid compared with that in plasma was related to the difference in protein concentrations in these 2 liquids (Wanwimolruk et al 1983). Few data in the literature concerned the implications of various conditions on the stereoselective binding of NSAIDs.…”
Section: Discussionmentioning
confidence: 93%
“…The binding of ibuprofen in plasma compared with synovial fluids depends on the concentrations of albumin in these compartments (Wanwimolruk et al 1983). There are differences in the affinity of S(?)…”
Section: Pharmacokinetics In Adultsmentioning
confidence: 99%